2016
DOI: 10.1051/0004-6361/201628540
|View full text |Cite
|
Sign up to set email alerts
|

Radiative levitation in carbon-enhanced metal-poor stars withs-process enrichment

Abstract: A significant fraction of all metal-poor stars are carbon-rich. Most of these carbon-enhanced metal-poor (CEMP) stars also show enhancement in elements produced mainly by the s-process (CEMP-s stars), and evidence suggests that the origin of these nonstandard abundances can be traced to mass transfer from a binary asymptotic giant branch (AGB) companion. Thus, observations of CEMP-s stars are commonly used to infer the nucleosynthesis output of low-metallicity AGB stars. A crucial step in this exercise is unde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 102 publications
(144 reference statements)
0
31
1
Order By: Relevance
“…In Matrozis & Stancliffe (2016) we showed that atomic diffusion should lead to very large abundance anomalies (e.g. [C/Fe] < −1) near the main sequence turn-off, a result clearly at odds with observational data.…”
Section: Comparison To Observationscontrasting
confidence: 59%
See 4 more Smart Citations
“…In Matrozis & Stancliffe (2016) we showed that atomic diffusion should lead to very large abundance anomalies (e.g. [C/Fe] < −1) near the main sequence turn-off, a result clearly at odds with observational data.…”
Section: Comparison To Observationscontrasting
confidence: 59%
“…In Matrozis & Stancliffe (2016) we showed how, in absence of other mixing processes, in most CEMP-s stars the carbon should settle out of the surface convection zone, while the surface abundance of iron should increase as a result of radiative levitation. Near the main sequence turn-off, before the convective envelope begins to move inwards in mass, the resulting abundances (e.g.…”
Section: Models With Atomic Diffusion and Thermohaline Mixingmentioning
confidence: 81%
See 3 more Smart Citations